AGENDA PENGEMBANGAN STUDI ISLAM DI PERGURUAN TINGGI: MEMPERTIMBANGKAN BERBAGAI TAWARAN MODEL INTEGRASI ILMU - Wardani, Wardani (UIN Antasari Banjarmasin, 2015)
Abstract : Basically, there are two approaches to study Islam either in textualsources (Quran and hadith) or in social and cultural expressions. Those arenormative and historical approach. This article suggests that the intensive andconstant dialogue between the twoby applying integrated, rich, syntheticIslamic and western approaches is a must to overcome the intellectual crisis inIslamic studies in Indonesia nowdays. In other words, Islam should not beviewed from one approach only, therefore, we need to build a bridgebetween Islamic religious sciences and secular ones (natural sciences, socialsciences, and humanities). The bridge should be two-fold, e.g. throughislamization of science and scientization of Islam. The first step meansthat we should make a room for scripture in scientific method, and that sciencesmust be value-laden. The second one means that Islamic religious sciences,such as theology, law, and ethics should be learned in the light of scientificstandard of inquiry.